Equality, Equity and Incentives: An Experiment - Loukas Balafoutas; Martin G. Kocher; Louis Putterman; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2010)
We devise a new experimental game by nesting a voluntary contributions mechanism in a broader spectrum of incentive schemes. With it, we study tensions between egalitarianism, equity concerns, self-interest, and the need for incentives. In a 2x2 design, subjects either vote on or exogenously encounter incentive settings while assigned unequal incomes that are either task-determined or random. We find subjects' voting to be mainly self-interested but also influenced by egalitarian and equity concerns, which sometimes cut in opposite directions. Contributions, which seem mainly determined by boundedly rational responses to incentives, are influenced by egalitarian, equity and strategic considerations.
Keywords: C91; C92; D31; D63; H41; 330; equality; efficiency; voluntary contribution mechanism; incentives; experiment; Soziale Ungleichheit; Rationales Verhalten; Verteilungsgerechtigkeit; Entscheidungstheorie; Test